2017
DOI: 10.1007/s00270-017-1856-1
|View full text |Cite
|
Sign up to set email alerts
|

Lymphangiography and Lymphatic Embolization for the Treatment of Refractory Chylous Ascites

Abstract: Lymphangiography and embolization can be used to treat chylous ascites. Identification of the site of leak is associated with significantly greater rate of clinical success compared to those whose site could not be identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
76
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 24 publications
1
76
0
1
Order By: Relevance
“…The published experience in the percutaneous treatment of postoperative CA is limited to case reports and retrospective series. 22,24,46 Majdalany et al recently reviewed the published experience for percutaneous treatment of traumatic CAs. They found 18 studies besides their cohort that included 96 patients with CA or CA associated with chylothorax, chylopericardium, or lymphoceles.…”
Section: Results Of Lymphatic Interventions In Patients With Chylous mentioning
confidence: 99%
See 3 more Smart Citations
“…The published experience in the percutaneous treatment of postoperative CA is limited to case reports and retrospective series. 22,24,46 Majdalany et al recently reviewed the published experience for percutaneous treatment of traumatic CAs. They found 18 studies besides their cohort that included 96 patients with CA or CA associated with chylothorax, chylopericardium, or lymphoceles.…”
Section: Results Of Lymphatic Interventions In Patients With Chylous mentioning
confidence: 99%
“…Studies have reported a detection rate of 55% for leakage sites in patients with CA. 22,24 This rate is lower compared with those patients with chylothorax. Anatomically, the intestinal and the hepatic lymphatic ducts that carry the chyle to join lumbar ducts or the cisterna chyli are often outside the pathway of the contrast that is injected in the groin lymph nodes.…”
Section: Clinical Complications and Diagnosis Of Chylous Ascitesmentioning
confidence: 85%
See 2 more Smart Citations
“…12,13 Successful treatments of pediatric chylothorax, chylous ascites, protein losing enteropathy, and plastic bronchitis are being increasingly described at different medical centers across the world. [14][15][16][17][18][19] These treatments involve novel approaches and utilize techniques that include retrograde transvenous lymphangiography, transcervical lymphangiography, thoracic duct stent-grafting, and balloon occlusion retrograde abdominal lymphangiography, among others. [20][21][22][23] The relationship of lymphatics with fluid balance, nutritional absorption, immunological function, endocrine organs, and spread of malignancy provides the potential to treat many more conditions.…”
mentioning
confidence: 99%